2017
DOI: 10.1038/s41598-017-07157-0
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of HIV-1 from Latency by an Ingenol Derivative from Euphorbia Kansui

Abstract: Cells harboring latent HIV-1 pose a major obstacle to eradication of the virus. The ‘shock and kill’ strategy has been broadly explored to purge the latent reservoir; however, none of the current latency-reversing agents (LRAs) can safely and effectively activate the latent virus in patients. In this study, we report an ingenol derivative called EK-16A, isolated from the traditional Chinese medicinal herb Euphorbia kansui, which displays great potential in reactivating latent HIV-1. A comparison of the doses u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 100 publications
1
33
0
Order By: Relevance
“…Importantly, kansui exhibits a strong synergy with HDACis or BETis, indicating that kansui can be used in combination with these LRAs to achieve a high level of HIV expression in latently infected cells [ 78 ]. Finally, using natural products such as kansui would greatly reduce the cost of treatment, which would contribute to providing affordable options to the patients in areas where expensive Western medicines cannot be accessible [ 123 ].…”
Section: Development Of Specific Therapymentioning
confidence: 99%
“…Importantly, kansui exhibits a strong synergy with HDACis or BETis, indicating that kansui can be used in combination with these LRAs to achieve a high level of HIV expression in latently infected cells [ 78 ]. Finally, using natural products such as kansui would greatly reduce the cost of treatment, which would contribute to providing affordable options to the patients in areas where expensive Western medicines cannot be accessible [ 123 ].…”
Section: Development Of Specific Therapymentioning
confidence: 99%
“…Figure 1A displays the structure of RVX-208 and PFI-1. To determine the effect of RVX-208 and PFI-1 on latent HIV-1 reactivation, we used J-Lat C11 cell line in which transcriptional activation of the latent provirus can be detected in individual cells by flow cytometry, since these cells harbor full-length latent HIV-1 provirus containing GFP gene in place of nef 13 , 24 27 . We found that both RVX-208 and PFI-1 robustly increased the level of GFP expression.…”
Section: Resultsmentioning
confidence: 99%
“…These assays were approved by Shanghai Public Health Clinical Center and Shanghai Changhai Hospital. Peripheral blood mononuclear cells (PBMCs) were isolated from fresh whole blood by density gradient centrifugation using Lympholyte®-H Cell Separation Media (Cedarlane Laboratories) as previously described 13 , 27 . CD4+ T cells were isolated from PBMCs by negative selection using CD4+ T cell Isolation Kit (Miltenyi Biotech).…”
Section: Methodsmentioning
confidence: 99%
“…C11 cells are a type of HIV-1 latently infected cells constructed by our lab. 8 , 27 , 28 , 29 , 30 , 31 , 32 YA were derived from Jurkat T cells infected with HIV-1 pseudovirus carrying the eGFP reporter gene. 8 , 27 Both of them were cultured in RPMI 1640 medium with 10% FBS (Gibco, Grand Island, NY, USA), 100 U/mL penicillin, and 100 μg/mL streptomycin (Invitrogen, Shanghai, China) at 37°C under 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%